High-Frequency Repetitive Transcranial Magnetic Stimulation Over the Left Dorsolateral Prefrontal Cortex Shortly Alleviates Fatigue in Patients With Multiple System Atrophy: A Randomized Controlled Trial - Pan, Jing; Mi, Tao-Mian; Ma, Jing-Hong; Sun, Hong; Chan, Piu (Frontiers in Neurology, 2022)
Background: Fatigue is a common symptom in patients with Multiple system atrophy, but effective treatments remain elusive. The present study aims to investigate whether high-frequency repetitive transcranial magnetic stimulation (rTMS) over the left dorsolateral prefrontal cortex could relieve fatigue in patients with Multiple system atrophy. Methods: This is a single-center, randomized and double-blind trial. Twenty-two patients with Multiple system atrophy and fatigue were randomly allocated to receive 10 sessions of either active (N=11) or sham (N=11) 10Hz rTMS over the left dorsolateral prefrontal cortex. The participants were assessed at baseline (T0), after the last session of treatment (T1), and at 2-week (T2) and 4-week (T3) follow-up timepoints. The primary outcomes were Fatigue Severity Scale-9 (FSS-9) scores, with Unified Multiple System Atrophy Rating Scale (UMSARS), 17-item Hamilton Depression Scale (HAMD-17), and Hamilton Anxiety Scale (HAMA) as secondary outcomes. Results: Two-way repeated ANOVAs revealed significant group × time interactions for FSS-9 scores (p < 0.001), HAMD-17 scores (p = 0.01) , HAMA scores (p = 0.01) and UMRSA part II (p=0.05). Post hoc analyses showed that compared to T0, the active group exhibited remarkable improvements in FSS-9 scores, HAMD-17, HAMA and UMRSA part II at T1 and T2, but not at T3. No significant improvement was found in the sham group. Conclusion: High-frequency rTMS over the left dorsolateral prefrontal cortex could provide short-term improvements for alleviating fatigue in patients with Multiple system atrophy, but the beneficial effects last no more than 4 weeks.